Peningkatkan Pemahaman Konsep Perkalian dengan Menggunakan Metode Demonstrasi Di Kelas III SD Negeri Cihaur II - rusmiati, nani (Journal of Innovation in Primary Education, 2023)
This research was motivated by the poor understanding of the concept of multiplication in class III at SD Negeri Cihaur II. The aim of this research is to determine the improvement of skills in understanding the concept of multiplication by applying the demonstration method in Class III of Cihaur II State Elementary School, Maja District, Majalengka Regency. The subjects in this research were 17 class III students at SDN Cihaur II, Maja District, Majalengka Regency. Data collection techniques use observation, interviews, tests, and documentation. The data analysis technique uses qualitative description. The results of the research show that: (1) The implementation of increasing understanding of the concept of multiplication by using the demonstration method in class III at SDN Cihaur II, Maja District, Majalengka Regency has proven to be able to increase students' understanding of the concept of multiplication, and (2) The application of the demonstration method in increasing understanding of the concept of multiplication in class. III SDN Cihaur II, Maja District, Majalengka Regency, has been proven to be able to increase students' understanding of concepts, this can be seen from the increase in class average scores from student test results at each stage of the cycle, namely, the class average score in cycle I was 48% and in cycle II it was 67% and cycle III 86%.